Beneficial effect of alloy disorder on the conversion efficiency of ZnO/ZnxCd1−xSe coaxial nanowire solar cells. Issue 12 (28th March 2015) - Bhutto, Waseem Ahmed; Wu, Zhiming; Cao, Yiyan; Wang, Weiping; He, Jialun; Luo, Qiang; Li, Shuping; Li, Heng; Kang, Junyong
<x xml:space="preserve">Abstract</x> The conversion efficiency of ZnO/ZnxCd1−xSe coaxial nanowire solar cells was improved by interfacial modification based on the alloy disorder effect.